In vitro screening for acetylcholinesterase inhibition of Baliospermum montanum, Humboldtia brunonis Wall. var. raktapushpa and Pittosporum viridulum - Biju John, Sulaiman CT, Sadashiva CT, Satheesh George and VRK Reddy (Journal of Applied Pharmaceutical Science, 2013)
Ethanolic extracts of three medicinal plants collected from South India were analyzed for their activity towards acetylcholinestrase (AChE) enzyme. The AChE inhibition was measured spectrophotometrically. All the three species namely, Baliospermum montanum, Humboldtia brunonis Wall. var. raktapushpa and Pittosporum viridulum showed substantial inhibitory activity towards acetylcholinesterase with IC50 values, 137.5µg/ml, 128.7 µg/ml and 105.3µg/ml, respectively.
Keywords: Baliospermum montanum, Humboldtia brunonis, Pittosporum viridulum,acetylcholinesterase inhibiters.